Role of acute respiratory diseases in pathogenesis of distal limb infections in cattle - A. D. Alekseev; O. G. Petrova; M. I. Barashkin; I. M. Milshtein; V. D. Moskvin (Ветеринария сегодня)
According to current concepts, ruminal and metabolic acidosis occur due to feeding cattle mainly with preserved acidic feeds such as silage and haylage. However, errors in feeding are not the only etiological factor leading to acidosis. In some cases, metabolic acidosis in cattle can develop along with respiratory infection caused by viral and bacterial agents. The main pathological processes resulting from acute respiratory diseases of cattle are bronchitises, tracheites and pneumonias. When the respiratory tract is affected in cattle, hypoxia occurs, causing intoxication and, thus, leading to ruminal acidosis. As a result, vasoactive substances (bacterial endotoxins, histamine, lactate) enter the bloodstream, the vascular endothelium is damaged due to the simultaneous expansion of arterioles and compression of venules, blood fluid is perfused from the vessels into the surrounding tissues, the blood flow in the microcirculatory bed is disrupted. An important role in the disturbance of blood circulation in small blood vessels is played by circulating immune complexes representing the «antigen-antibody» complex. Low molecular weight circulating immune complexes settle in various organs and tissues of the body, lead to inflammation and damage the normal tissue structure. Most frequently, immune complexes affect the endothelium of blood vessels, renal glomeruli and joints. Distal limb vessels are primarily affected in cattle, leading to disturbance of skin trophism of the limbs and hooves, development of laminitis, while the hoof horn is weakly keratinized and cannot resist aggressive mechanical and chemical environmental factors. Damaged hooves are the gateway of infection for the agents of necrobacteriosis (Fusobacterium necrophorum), staphylococcosis (Staphylococcus spp.), streptococcosis (Streptococcus spp.) and other pathogens. In addition, favorable conditions evolve for the development of mixed infection due to reduction in the overall organism resistance, which is observed for both respiratory and distal limb infections.